Edukasi Aman Berinternet Bagi Remaja Sekolah Menengah Pertama Secara Daring - Titin Setiawati (Universitas Prof. Dr. Moestopo (Beragama), 2022)
The use of internet-based communication media is growing rapidly, so it is called the communication revolution. The positive impact of this massive development is the ease of communication. However, it also has negative impacts. One of the negative impacts is the use of the internet among adolescent students who are emotionally immature. This condition is often accompanied by the lack of internet rules and ethical knowledge that could pose a dangerous situation because these teenagers have the potential to become victims or perpetrators of internet crimes. One possible way to reduce the negative impact is by holding community service in the form of training and discussions on Safe Internet for the Youth at Muhammadiyah Junior High School Gunung Putri. With the aim of increasing awareness to use internet media safely, activities are carried out by providing knowledge about internet rules and ethics, recognizing hoaxes, and strengthening from the religious side.